Extractor Solutions Improve the Extraction/Quantification of Microbial Load by Conventional Cultivation Techniques - Alves, Adriana Barboza; Machado, Alan Rodrigues Teixeira; Ferreira, Osania Emerenciano (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Limitations in quantifying microorganisms in conventional soil microbiological analyses cause experimental errors. There is a difficulty in performing the correct dilution of the sample, which is influenced by the specific granulometric characteristics of each soil. This study aimed to evaluate different combinations of extracting soil solutions. Clayey loam and sandy loam are the two types of soil evaluated according to current humidity, pH, and granulometric analysis. For the quantification of the Colony Forming Units (CFU g-1) of the soil, extracting solutions of H2O (distilled water), NaCl (sodium chloride), Na4P2O7 (sodium pyrophosphate), and C64H124O26 (Polysorbate Tween-80) were used for analyses. The method of in-depth serial dilution was used in this study to quantify the microorganisms. The means of each microbiological feature were examined and compared using the Tukey test with a 5% chance of being correct. The granulometric characteristics of the soil affected the microbial quantification. The solution of H2O + Na4P2O7 + C64H124O26 allowed greater quantification for sandy loam soils, and for clayey loam soil, the solution of H2O + Na4P2O7 was the most efficient.